Simplify it all

Algebra Level 3

Let x , y x , y and z z be positive real numbers that satisfy

2 log x ( 2 y ) = 2 log 2 x ( 4 z ) = log 2 x 4 ( 8 y z ) 0 \large 2 \log_{x}{ (2y) } = 2 \log_{2x}{ (4z) } = \log_{2x^4}{ (8yz) } \not = 0

If the value of x y 5 z xy^5z can be expressed in the form 1 2 p / q \dfrac{1}{2^{p/q}} , where p p and q q are relatively prime positive integers, find p + q p +q .


The answer is 49.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Nick Kent
Aug 5, 2019

Let's convert the logarithms to base 2:

2 log 2 ( 2 y ) log 2 ( x ) = 2 log 2 ( 4 z ) log 2 ( 2 x ) = log 2 ( 8 y z ) log 2 ( 2 x 4 ) 0 2 log 2 ( 2 ) + 2 log 2 ( y ) log 2 ( x ) = 2 log 2 ( 4 ) + 2 log 2 ( 4 ) log 2 ( 2 ) + log 2 ( x ) = log 2 ( 8 ) + log 2 ( y ) + log 2 ( z ) log 2 ( 2 ) + 4 log 2 ( x ) 0 \frac { 2\log _{ 2 }{ \left( 2y \right) } }{ \log _{ 2 }{ \left( x \right) } } =\frac { 2\log _{ 2 }{ \left( 4z \right) } }{ \log _{ 2 }{ \left( 2x \right) } } =\frac { \log _{ 2 }{ \left( 8yz \right) } }{ \log _{ 2 }{ \left( 2{ x }^{ 4 } \right) } } \neq 0\\ \frac { 2\log _{ 2 }{ \left( 2 \right) } +2\log _{ 2 }{ \left( y \right) } }{ \log _{ 2 }{ \left( x \right) } } =\frac { 2\log _{ 2 }{ \left( 4 \right) } +2\log _{ 2 }{ \left( 4 \right) } }{ \log _{ 2 }{ \left( 2 \right) } +\log _{ 2 }{ \left( x \right) } } =\frac { \log _{ 2 }{ \left( 8 \right) } +\log _{ 2 }{ \left( y \right) } +\log _{ 2 }{ \left( z \right) } }{ \log _{ 2 }{ \left( 2 \right) } +4\log _{ 2 }{ \left( x \right) } } \neq 0

Let a = log 2 ( x ) , b = log 2 ( y ) , c = log 2 ( z ) a=\log _{ 2 }{ \left( x \right) } ,b=\log _{ 2 }{ \left( y \right) } ,c=\log _{ 2 }{ \left( z \right) } . Then:

2 + 2 b a = 4 + 2 c 1 + a = 3 + b + c 1 + 4 a 0 \frac { 2+2b }{ a } =\frac { 4+2c }{ 1+a } =\frac { 3+b+c }{ 1+4a } \neq 0 , meaning b 1 b\neq -1

Now we've a system with two equations:

{ ( 1 + a ) 2 ( 1 + b ) = 2 ( 2 + c ) a ( 1 + 4 a ) 2 ( 1 + b ) = ( 3 + b + c ) a { 1 + a + b + a b = 2 a + a c 2 + 8 a + 2 b + 8 a b = 3 a + a b + a c { a c = 1 a + b + a b a c = 2 + 5 a + 2 b + 7 a b 2 + 5 a + 2 b + 7 a b = 1 a + b + a b 1 + 6 a + b + 6 a b = 0 ( 1 + 6 a ) ( 1 + b ) = 0 \begin{cases} \left( 1+a \right) \cdot 2\left( 1+b \right) =2\left( 2+c \right) \cdot a \\ \left( 1+4a \right) \cdot 2\left( 1+b \right) =\left( 3+b+c \right) \cdot a \end{cases}\\ \begin{cases} 1+a+b+ab=2a+ac \\ 2+8a+2b+8ab=3a+ab+ac \end{cases}\\ \begin{cases} ac=1-a+b+ab \\ ac=2+5a+2b+7ab \end{cases}\\ 2+5a+2b+7ab=1-a+b+ab\\ 1+6a+b+6ab=0\\ \left( 1+6a \right) \cdot \left( 1+b \right) =0

Since b 1 b\neq -1 , we know a = 1 6 a=-\frac { 1 }{ 6 } :

1 6 c = 1 + 1 6 + b 1 6 b c = 7 5 b -\frac { 1 }{ 6 } \cdot c=1+\frac { 1 }{ 6 } +b-\frac { 1 }{ 6 } \cdot b\\ c=-7-5b

Now we can get the answer:

x y 5 z = 2 a + 5 b + c = 2 1 6 + 5 b 7 5 b = 2 1 6 7 = 2 43 6 = 1 2 43 6 x\cdot { y }^{ 5 }\cdot z={ 2 }^{ a+5b+c }={ 2 }^{ -\frac { 1 }{ 6 } +5b-7-5b }={ 2 }^{ -\frac { 1 }{ 6 } -7 }={ 2 }^{ -\frac { 43 }{ 6 } }=\frac { 1 }{ { 2 }^{ \frac { 43 }{ 6 } } }

p = 43 , q = 6 p + q = 49 p=43,q=6\Rightarrow p+q=\boxed { 49 }

Step 1: Let n = 2 log x ( 2 y ) = 2 log 2 x ( 4 z ) = log 2 x 4 ( 8 y z ) 0 n = 2 \log_{x}{ (2y) } = 2 \log_{2x}{ (4z) } = \log_{2x^4}{ (8yz) } \not = 0

Step 2: Convert each of the expressions to an exponential for our simplification

Expression 1: n = 2 log x ( 2 y ) x n / 2 = 2 y n = 2 \log_{x}{ (2y) } \implies x^{n/2} = 2y

Expression 2: n = 2 log 2 x ( 4 z ) ( 2 x ) n / 2 = 4 z n = 2 \log_{2x}{ (4z) } \implies (2x)^{n/2} = 4z

Expression 3: n = log 2 x 4 ( 8 y z ) ( 2 x 4 ) n = 8 y z n = \log_{2x^4}{ (8yz) } \implies (2x^4)^{n} = 8yz [Note: E1 × E2 = E3 ] \color{#3D99F6} \text{ [Note: E1 } \times \text{ E2 = E3 ]}

Step 3: Thus as E1 × \times E2 = E3

\implies Products of E1 × \times E2 = E3

2 n / 2 x n = 2 n x 4 n x 3 n = 2 n / 2 \implies 2^{n/2} \cdot x^n = 2^n x^{4n} \implies \color{#EC7300} x^{3n} = 2^{-n/2} x = 2 1 / 6 \implies x = 2^{-1/6}

Step 4: Lets get back to the question :)

We have substituted the "expressions" and raised it to the required power.

x y 5 z = 2 1 / 6 × ( x 5 n / 2 2 5 ) × ( 2 n / 2 x n / 2 2 2 ) xy^5 z = 2^{-1/6} \times (x^{5n/2} \cdot 2^{-5} ) \times (2^{n/2} \cdot x^{n/2} \cdot 2^{-2} ) For easiness of simplification I have separated the bases of powers \small \color{#20A900} \text{ For easiness of simplification I have separated the bases of powers }

x y 5 z = 2 43 / 6 × x 3 n × 2 n / 2 Notice a similarity with the above orange expression this is = 1 xy^5 z = 2^{-43/6} \times x^{3n} \times 2^{n/2} \small \color{#EC7300} \text{ Notice a similarity with the above orange expression} \therefore \text {this is = 1 }

Step 5: Find the value of p + q p + q

Hence: x y 5 z = 2 43 / 6 = 1 2 43 / 6 xy^5 z = 2^{-43/6} = \dfrac{1}{2^{43/6}} and by substitution p + q = 49 p + q = \boxed{ 49 }

Nice solution. Loved it

James Bacon - 1 year, 10 months ago

Let 2 log x ( 2 y ) = 2 log 2 x ( 4 x ) = log 2 x 4 ( 8 y z ) = 2 k 2 \log_x (2y) = 2 \log_{2x} (4x) = \log_{2x^4} (8yz) = 2k . Using a log base of 2, we have:

{ log 2 ( 2 y ) log 2 x = k log 2 ( 2 y ) = k log 2 x . . . ( 1 ) log 2 ( 4 z ) log 2 ( 2 x ) = k log 2 ( 4 z ) = k log 2 ( 2 x ) . . . ( 2 ) log 2 ( 8 y z ) log 2 ( 2 x 4 ) = 2 k log 2 ( 2 y ) + log 2 ( 4 z ) = 2 k log 2 ( 2 x 4 ) . . . ( 3 ) \begin{cases} \dfrac {\log_2(2y)}{\log_2 x} = k & \implies \log_2 (2y) = k \log_2 x & ...(1) \\ \dfrac {\log_2(4z)}{\log_2 (2x)} = k & \implies \log_2 (4z) = k \log_2 (2x) & ...(2) \\ \dfrac {\log_2(8yz)}{\log_2 (2x^4)} = 2k & \implies \log_2 (2y) + \log_2 (4z) = 2k \log_2 (2x^4) & ...(3) \end{cases}

From ( 1 ) + ( 2 ) = ( 3 ) (1)+(2) = (3) :

k log 2 x + k log 2 ( 2 x ) = 2 k log 2 ( 2 x 4 ) Since k 0 log 2 x + log 2 ( 2 x ) = 2 log 2 ( 2 x 4 ) log 2 ( 2 x 2 ) = log 2 ( 4 x 8 ) 2 x 2 = 4 x 8 x 6 = 1 2 x = 1 2 1 6 \begin{aligned} k \log_2 x + k \log_2(2x) & = 2k \log_2(2x^4) & \small \color{#3D99F6} \text{Since }k \ne 0 \\ \log_2 x + \log_2(2x) & = 2 \log_2(2x^4) \\ \log_2(2x^2) & = \log_2(4x^8) \\ 2x^2 & = 4x^8 \\ x^6 & = \frac 12 \\ \implies x & = \frac 1{2^\frac 16} \end{aligned}

From ( 1 ) ÷ ( 2 ) (1) \div (2) :

log 2 ( 2 y ) log 2 ( 4 z ) = log 2 x 1 + log 2 x = 1 6 1 1 6 = 1 5 Since log 2 x = 1 6 5 log 2 ( 2 y ) = log 2 ( 4 z ) 5 log 2 ( 2 y ) + log 2 ( 4 z ) = 0 log 2 ( 2 5 y 5 2 2 z ) = 0 2 7 y 5 z = 1 y 5 z = 1 2 7 x y 5 z = 1 2 7 + 1 6 = 1 2 43 6 \begin{aligned} \frac {\log_2 (2y)}{\log_2 (4z)} & = \frac {\log_2 x}{1 + \log_2 x} = \frac {-\frac 16}{1-\frac 16} = - \frac 15 & \small \color{#3D99F6} \text{Since }\log_2 x = - \frac 16 \\ 5 \log_2 (2y) & = - \log_2 (4z) \\ 5 \log_2 (2y) + \log_2 (4z) & = 0 \\ \log_2 (2^5y^5 \cdot 2^2 z) & = 0 \\ 2^7y^5z & = 1 \\ y^5z & = \frac 1{2^7} \\ \implies xy^5z & = \frac 1{2^{7+\frac 16}} = \frac 1{2^\frac {43}6} \end{aligned}

Therefore, p + q = 43 + 6 = 49 p+q = 43+6 = \boxed{49} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...